2023
DOI: 10.1002/chem.202203963
|View full text |Cite
|
Sign up to set email alerts
|

Across the Dimensions: A Three‐Component Self‐Assembly of Pentaphosphaferrocene‐based Coordination Polymers

Abstract: Pentaphosphaferrocenes [Cp R Fe(η 5 -P 5 )] (Cp* = η 5 -C 5 Me 5 ) (A), Cp'' = η 5 -C 5 H 3 tBu 2 -1,3 (B)) are excellent building blocks for polymeric assemblies in supramolecular chemistry in combination with coinage metal salts of weakly coordinating anions such as AgSbF 6 . Adding rigid aromatic dinitriles ortho/meta/para-(NC) 2 C 6 H 4 in a one-pot reaction between [Cp R Fe(η 5 -P 5 )] and AgSbF 6 leads to various coordination polymers (CPs) by a three-component self-assembly. The sterical demand of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…o-DFB and CD 2 Cl 2 were distilled from CaH 2 and other solvents were directly taken from an MBraun SPS-800 solvent purification system and degassed at room temperature prior to use. Solution 1 H (400.130 MHz), 11 B (128.379 MHz), 13 C (100.627 MHz), 19 F (376.498 MHz) and 31 P (161.976 MHz) NMR spectra were recorded on a Bruker Avance400 spectrometer using (H 3 C) 4 Si ( 1 H, 13 C), BF 3 •Et 2 O ( 11 B), CFCl 3 ( 19 F) or 85% phosphoric acid ( 31 P), respectively, as external standards. Chemical shifts (δ) are provided in parts per million (ppm) and coupling constants (J) are reported in Hertz (Hz).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…o-DFB and CD 2 Cl 2 were distilled from CaH 2 and other solvents were directly taken from an MBraun SPS-800 solvent purification system and degassed at room temperature prior to use. Solution 1 H (400.130 MHz), 11 B (128.379 MHz), 13 C (100.627 MHz), 19 F (376.498 MHz) and 31 P (161.976 MHz) NMR spectra were recorded on a Bruker Avance400 spectrometer using (H 3 C) 4 Si ( 1 H, 13 C), BF 3 •Et 2 O ( 11 B), CFCl 3 ( 19 F) or 85% phosphoric acid ( 31 P), respectively, as external standards. Chemical shifts (δ) are provided in parts per million (ppm) and coupling constants (J) are reported in Hertz (Hz).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Current approaches in supramolecular chemistry focus on the use of nitrogen-, oxygen-, and/or sulfur-containing organic linkers to connect different metal centers. During the last decades, our group has demonstrated that organometallic E n (E = heavier group 15 element) ligand complexes are excellent building blocks for supramolecular assemblies as well . Indeed, many examples of the coordination chemistry of E n ( n = 1–6) ligand complexes toward coinage metal salts, also in combination with organic linkers, were reported during the past two decades. , This novel approach allowed the synthesis of a large library of aggregates including polymeric (1D, 2D , and 3D coordination polymers) and discrete (monomeric, dimeric or spherical aggregates as well as nanobowls) supramolecular assemblies. While the coinage metal salts of Cu I /Ag I /Au I have already been extensively utilized in these studies, the monovalent ions of the heavier group 13 elements, namely In I and Tl I , have only recently attracted general interest within the field of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation